Tert-Butyl thiol and pyridine ligand co-protected 50-nuclei clusters: the effect of pyridines on Ag–SR bonds. Issue 36 (27th August 2020) - Shen, Yang-Lin; Jin, Jun-Ling; Xie, Yun-Peng; Lu, Xing
Abstract : The presence of pyridine ligands induces expansion of AgN –SR bond lengths compared to that of AgO –SR without pyridines, which has been proved to profoundly influence the construction of thiolate–silver(i ) compounds. Abstract : Constructing silver(i )–thiolate clusters from simple building blocks usually involves elusive self-assembly processes and remains a long-standing challenge. In this work, we report 6 silver(i )–thiolate clusters protected by pyridines, namely, [Ag3 ( t BuS)2 (Py)(NO3 )] n (Py = pyridine) (1 ), [Ag10 ( t BuS)6 (Py)6 (CF3 CO2 )4 ]·3Py (2 ), [Ag12 ( i PrS)6 (Py)8 (NO3 )6 ]·2H2 O (3 ), Ag12 ( i PrS)6 (Py)8 (CF3 CO2 )6 (4 ), Ag12 ( i PrS)6 (4-ap)6 (NO3 )6 (4-ap = 4-aminopyridine) (5 ), and [Ag50 S13 ( t BuS)20 (Py)12 ]·4BF4 ·4Py·4CH3 OH·2H2 O (6 ). Single-crystal X-ray crystallography analysis reveals that six clusters are constructed by four types of structural blocks, including the PyAg( t BuS)2 monomer, Py2 Ag2 ( t BuS)2 dimer, Py3 Ag3 ( t BuS)3 trimer and (4-ap)6 Ag6 ( i PrS)6 hexamer. Notably, cluster 6 consists of a rhombic dodecahedron S@Ag14 kernel with 12 interstitial S 2− atoms encapsulated by 8 μ4 - t BuS − ligands, as well as six unique butterfly-like (Py)2 Ag6 ( t BuS)2 staple motifs composed of a Py2 Ag2 ( t BuS)2 dimer and four silver ions. Moreover, it is found that pyridine ligands have important influence on the construction of silver thiolate clusters and their Ag–SR bond lengths.